Handbook of research on global fashion management and merchandising - Vecchi, Alessandra; Buckley, Chitra 1959- (A volume in the Advances in Logistics, Operations, and Management Science (ALOMS) Book Series, 2016)
"This book explores the various facets of effective management procedures within the fashion industry, featuring research on entrepreneurship, operations management, marketing, business modeling, and fashion technology"-- Provided by publisher.